Green Marketing Innovation and Eco-Friendly Products on Purchase Intention of Skincare in the Era of Sustainable Economy: Inovasi Green Marketing dan Produk Ramah Lingkungan terhadap Minat Beli Skincare di Era Ekonomi Berkelanjutan - Zefana; Hommy Dorthy Ellyany Sinaga; Brillian Moktar (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study analyzes the impact of green marketing innovation and eco-friendly product attributes on consumer purchase intention in the skincare industry in the sustainable economy era. A quantitative method was employed by distributing questionnaires to 110 Somethinc customers at Vanilla Skincare & Cosmetic Store, with respondents selected based on their familiarity with experience with the products. The instruments were tested for validity and reliability, and data analysis was performed using multiple linear regression with SPSS 27.The findings show that green marketing has a positive but insignificant influence on purchase intention. Campaigns such as collaboration with LindungiHutan and the EmptyBox program helped strengthen brand awareness but did not substantially affect consumer decisions. In contrast, eco-friendly products demonstrated a positive and significant effect. Factors including quality, the use of natural ingredients, recyclable packaging, and proven skin health benefits were the main drivers of consumer purchase interest. Overall, the research concludes that sustainability and product quality play a greater role than promotional strategies in shaping buying decisions. These results suggest that skincare companies should continue to innovate in eco-friendly product development while reinforcing sustainable marketing to build long-term consumer trust.